Sizing up the boutique hotel industry in Singapore. - Koh, Rebecca Mei Li. (2009)
The boutique hotel sector is regarded as a niche segment of the hospitality industry and has increasingly become a popular choice of accommodation among developers and hotel guests worldwide in recent years. With growing interests in this market by the various stakeholders that include government organizations, chain hotels, entrepreneurs and potential guests, certain management issues pertaining to local development and operations have arisen. As there is a lack of research in this niche area, especially in the local context, this research attempts to shed light on the uniqueness of boutique hotel attributes and development. A qualitative approach comprising extensive literature review and interviews with industry professionals was undertaken for this research. This report focuses on identifying critical success factors of local boutique hotels. A decision flow model is eventually proposed to assist potential boutique hoteliers in the development of their boutique hotel establishment.